Mammary and splenic neoplasms in a female dog: Case reportt - Machado, Nathália Borstmann; Lehmen, Daniela (Pubvet, 2024)
Regarding mammary and splenic neoplasms in dogs, the surgical therapeutic approach is often the method of choice, given its curative potential and the possibility of subsequent histopathological analysis. In veterinary medicine, the incidence of mammary neoplasms is high, especially in unneutered female dogs. Breast carcinoma in situ, with its histological particularities and clinical behavior, requires a careful diagnosis and precise therapeutic approach, carrying out additional tests such as cytopathology and ultrasound to adequately define the treatment. Surgical excision, associated with the evaluation of adjacent healthy breast tissue, is essential to ensure complete removal of the neoplastic tissue, plus ovariohysterectomy (OVH) is also indicated in addition to a mastectomy. Spleen tumors are similarly common in dogs, especially hemangiosarcoma which is notable for its aggressiveness and high metastatic rate. Therefore, early diagnosis and precise intervention are essential for a good prognosis, with the affected organ being often removed in its entirety. Therefore, we report the case of a female Shih-Tzu dog, 7 years old and weighing 4kg, who presented a nodule in the left M3 upon palpation, measuring
Keywords: carcinoma; hemangiosarcoma; mastectomy; ovariohysterectomy; spleen; splenectomy